2020
DOI: 10.5937/jpea24-29626
|View full text |Cite
|
Sign up to set email alerts
|

Grain properties of new inbred lines in comparison with maize hybrids

Abstract: Grain quality parameters of five new maize inbred lines were investigated and compared with the corresponding properties of two commercial hybrids used in flour production. Kernel of the line L2 had the highest 1000-kernel mass (267.54 g), and line L2 had the highest test mass (844.68 kg m-3 ). The milling response ranged from 9.80 (L2) to 14.03 s (L1). The largest share of the soft fraction of endosperm was determined in L3 (37.13 %), which is slightly lower than in hybrid ZP 633. The highest protein (12.37 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Regarding this trait, hybrids differed greatly within the small fraction as compared to differences between large fractions. Besides the effect of hybrid, a great influence on 1000 seed weight is reported for different environmental factors (drought stress, and insufficient lighting), especially after silking, (Keszthelyi et al, 2022;Nikolić, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this trait, hybrids differed greatly within the small fraction as compared to differences between large fractions. Besides the effect of hybrid, a great influence on 1000 seed weight is reported for different environmental factors (drought stress, and insufficient lighting), especially after silking, (Keszthelyi et al, 2022;Nikolić, et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Different corn varieties' endosperms differ greatly in terms of the protein matrix thickness, hardness, thickness of the peripheral layers, cell sizes, and protein components [27], which was confirmed by our research as well. However, a previous investigation by Nikolić et al [28] showed that the protein content in the kernels of different corn hybrids ranged from 8.63 to 10.72%. In addition, the results of Watson [27] indicated that the commodity yellow dent corn on a dry matter basis has 9.5% protein.…”
Section: Chemical Composition Of Baby Corn Samplesmentioning
confidence: 93%